Proteomic Analysis of Myocardia Containing the Obscurin R4344Q Mutation Linked to Hypertrophic Cardiomyopathy - Hu, Li-Yen R.; Kontrogianni-Konstantopoulos, Aikaterini (Frontiers in Physiology, 2020)
Obscurin is a giant cytoskeletal protein with structural and regulatory roles encoded by the OBSCN gene. Recently, mutations in OBSCN were associated with the development of different forms of cardiomyopathies, including hypertrophic cardiomyopathy (HCM). We previously reported that homozygous mice carrying the HCM-linked R4344Q obscurin mutation develop arrhythmia by 1-year of age under sedentary conditions characterized by increased heart rate, frequent incidents of premature ventricular contractions, and episodes of spontaneous ventricular tachycardia. In an effort to delineate the molecular mechanisms that contribute to the observed arrhythmic phenotype, we subjected protein lysates prepared from left ventricles of 1-year old R4344Q and wild-type mice to comparative proteomics analysis using tandem mass spectrometry; raw data are available via ProteomeXchange with identifier PXD017314. We found that the expression levels of proteins involved in cardiac function and disease, cytoskeletal organization, electropotential regulation, molecular transport and metabolism were significantly altered. Moreover, phospho-proteomic evaluation revealed changes in the phosphorylation profile of Ca2+ cycling proteins, including sAnk1.5, a major binding partner of obscurin localized in the sarcoplasmic reticulum; notably, this is the first report indicating that sAnk1 undergoes phosphorylation. Taken together, our findings implicate obscurin in diverse cellular processes within the myocardium, which is consistent with its multiple binding partners, localization in different subcellular compartments, and disease association.